Cryopreserved Allogeneic Bone Marrow As Novel Target of Immune Modulating Activity of Fetal Liver Cells - Goltsev, A. N.; Ostankova, L. V.; Matsevitaya, I. Yu.; Dubrava, T. G. (Problems of Cryobiology and Cryomedicine, 2008)
Modulating activity of fetal liver cells at co-transplantation with cryopreserved allogeneic bone marrow was experimentally proved. This co-transplantation increases hemopoietic potential of allogeneic bone marrow and reduces its immune reactivity, manifesting in the activity of â€œgraft versus hostâ€ reaction and rise in the survival of recipients.